Midazolam and its effect on vital signs and behavior in children under conscious sedation in dentistry - Vasakova, J; Duskova, J; Lunackova, J; Drapalova, K; Zuzankova, L; Starka, L; Duskova, M; Broukal, Z (Physiological research, 2020)
Midazolam is a short acting sedative with small number of adverse effects. Administered orally, it is currently the most common form of conscious sedation in children. The objective of this paper is to describe effect of midazolam administered to children during dental treatment on their vital signs, and to monitor changes in children's behavior. We described values of vital signs and behavior in 418 sedations conducted in 272 children between 1-12 years of age. To achieve the following results, we used data from 272 all first-time sedations. After administration of midazolam arterial blood pressure and blood oxygen saturation decreased by values which were not clinically significant. The heart rate increased, with values staying within the limits of physiological range. The speed of onset of midazolam's clinical effects depends on age and dose. The lower age and dose correlated with the higher behavior score. The effectiveness of midazolam treatment is 97.8 %. Unwillingness of child to receive midazolam is predictor for disruptive behavior during sedation. 1.8 % of all sedation cases showed paradoxical reactions. The administration of midazolam in dose of 0.5 mg per 1 kg of child's body weight is safe and could be recommended for dental treatment in pediatric dentistry.
Keywords: zubní lékařství; Infant; Humans; kojenec; hypnotika a sedativa; dítě; Midazolam; analgosedace; Child; Female; Hypnotics and Sedatives; Administration, Oral; lidé; Conscious Sedation; vitální znaky; chování dětí; předškolní dítě; midazolam; ženské pohlaví; Male; Vital Signs; aplikace orální; mužské pohlaví; Child Behavior; Child, Preschool; Dentistry